The Impact of Cash Flows on the State and Results of the Financial Activity of the Enterprise - Qudratovich, Eshonqulov Akmal (European Journal of Life Safety and Stability (2660-9630), 2022)
The results of production, commercial, financial and other types of economic activity depend on various factors that are to varying degrees dependent on each other. Of particular importance in the efficiency of the functioning of the organization is the control of its cash flows.